Finite Element Modeling and Decoupled Seismic Stability Analysis of a Zoned Rockfill Dam Designed By Traditional Empirical Methods - Dhakal, Shanker; Bhandary, N. P.; Yatabe, R.; Pradhan, P. L.; Tiwari, R. C. (Journal of the Institute of Engineering, 2011)
Despite the recommendation made by ICOLD a few decades ago, the high and important zoned rockfill dams, either existing or proposed, located in the region of high seismicity like Nepal, have been found still designed simply by following the traditional empirical methods. The authors, having identified this gap, became interested to carry out a research to know: how such dams would perform when their seismic safety was evaluated by dynamic analysis in terms of crest settlement, which might lead to the loss of freeboard and hence the overtopping (collapse) of the structure. Also, as a secondary objective, the authors wished to address: how the effective geometry of the dam foundation in the structural model may be determined when flexibility of foundation is considered by trial and error ‘vertical stress criterion’. This paper puts forth the summary of the research. The seismic safety is evaluated by adopting a simplified technique (‘decoupled seismic deformation analysis’) where the peak crest acceleration response obtained from the time history analysis of the 2D plain strain finite element model (both with and without foundation flexibility considered) is utilized to predict the potential permanent deformation (settlement) of crest using the method based on Newmark’s Analysis Procedure. Key words: Zoned rockfill dam; Seismic deformation analysis; Finite element method; Displacement Decoupling; Time history analysis DOI: http://dx.doi.org/10.3126/jie.v8i1-2.5098 Journal of the Institute of Engineering Vol. 8, No. 1&2, 2010/2011 Page: 71-92 Uploaded Date: 19 July, 2011